2004
DOI: 10.1023/b:visi.0000004832.02269.45
|View full text |Cite
|
Sign up to set email alerts
|

Learning from User Behavior in Image Retrieval: Application of Market Basket Analysis

Abstract: This article describes an approach to learn feature weights for content-based image retrieval (CBIR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In our particular domain of application, NASA's Solar Dynamics Observatory (SDO) mission generates approximately 69,000 images per day, thus making the task of hand labeling them (meta-data generation) impossible, and making it a relevant problem for CBIR. There are several important surveys on CBIR [5,6,7,8], but we found that until [1], there has not been new work done in CBIR. For the domain specific problem of solar images that this framework was originally developed for, we referred to surveys of high-dimensional indexing of multimedia data [9] and applications to medicine [10], which fit the constraints of our particular application.…”
Section: Introductionmentioning
confidence: 99%
“…In our particular domain of application, NASA's Solar Dynamics Observatory (SDO) mission generates approximately 69,000 images per day, thus making the task of hand labeling them (meta-data generation) impossible, and making it a relevant problem for CBIR. There are several important surveys on CBIR [5,6,7,8], but we found that until [1], there has not been new work done in CBIR. For the domain specific problem of solar images that this framework was originally developed for, we referred to surveys of high-dimensional indexing of multimedia data [9] and applications to medicine [10], which fit the constraints of our particular application.…”
Section: Introductionmentioning
confidence: 99%
“…Also, and are similar to each other in that they are accessed by users and , but not by and . Similar ideas have been successfully applied to image retrieval to improve the accuracy of similarity measurement [12], [13], [25].…”
Section: A Audio Similaritymentioning
confidence: 99%
“…Consequently, one of the major challenges in CBIR is how to compensate for the semantic gap using the low-level features. Several different similarity functions using low-level features have been proposed and examined [12,19,28]. Nevertheless, as Santini et al argued in [20], the only perceptual similarity that can meaningfully be used is pre-attentive similarity, not semantic similarity.…”
Section: Introductionmentioning
confidence: 99%